2005
DOI: 10.1074/jbc.m413123200
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Pore Region Modify Epithelial Sodium Channel Gating by Shear Stress

Abstract: Previous studies have shown that epithelial Na؉ channels (ENaCs) are activated by laminar shear stress (LSS). ENaCs with a high intrinsic open probability because of a mutation (␤S518K) or covalent modification of an introduced Cys residue (␣S580C) in the pre-second transmembrane domain (pre-M2) were not activated by LSS, suggesting that the pre-M2 region participates in conformational rearrangements during channel activation. We examined the role of the pore region of the ␣-subunit in channel gating by studyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 61 publications
5
47
0
Order By: Relevance
“…In contrast, ␣␤␥M438V channels spend most of the time in the open state with rare short closures, leading to a very high P o (0.95 Ϯ 0.02, n ϭ 6). The double mutants behave like WT mENaC with the estimated P o of 0.29 Ϯ 0.02 (n ϭ 4), which is close to the value we reported recently under similar conditions (0.37 Ϯ 0.06) (11,23). All of the mutants had unitary currents (0.53 Ϯ 0.02 pA, n ϭ 6 for ␣G481M␤␥; 0.50 Ϯ 0.01 pA, n ϭ 6 for The numbers below each current decay are the Na ϩ concentrations (in mM) used for inducing self-inhibition.…”
Section: Substitutions At ␣Glysupporting
confidence: 73%
“…In contrast, ␣␤␥M438V channels spend most of the time in the open state with rare short closures, leading to a very high P o (0.95 Ϯ 0.02, n ϭ 6). The double mutants behave like WT mENaC with the estimated P o of 0.29 Ϯ 0.02 (n ϭ 4), which is close to the value we reported recently under similar conditions (0.37 Ϯ 0.06) (11,23). All of the mutants had unitary currents (0.53 Ϯ 0.02 pA, n ϭ 6 for ␣G481M␤␥; 0.50 Ϯ 0.01 pA, n ϭ 6 for The numbers below each current decay are the Na ϩ concentrations (in mM) used for inducing self-inhibition.…”
Section: Substitutions At ␣Glysupporting
confidence: 73%
“…Previous studies from our group have suggested that TM2 and adjacent residues have important roles in the response of ENaC to LSS as both the magnitude and kinetics of the LSS response were altered by substitutions introduced within this region (43,44). Interestingly, the magnitude of the LSS response of the MEC-4d/MEC-10 channel was not altered by replacing the TM2 and C terminus of MEC-10 with the corresponding region of MEC-4 (MEC-10-4TM2C chimera) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ENaC is activated by shear stress in native kidney tubules, endothelial cells, and heterogeneous expression systems (26,41,42). ENaC gating in response to LSS was altered by mutations introduced at key sites within the large ECD and transmembrane helices (43)(44)(45)(46). We have proposed a model where LSS-induced motions within the extracellular region of ENaC lead to movement of the transmembrane helices where the channel gate resides, transitioning the channel to a higher P o state (22).…”
Section: Discussionmentioning
confidence: 99%
“…Cell-attached Patch Clamp Measurements-1.5-4 h after microinjection of ENaC-expressing oocytes with either K-gluconate or K-ZMP and after removal of their vitelline membranes, single channel patch-clamp recordings in the cell-attached mode were performed using identical bath and pipette solutions with LiCl as the predominant salt, as previously described (33). Cell-attached recordings were generally performed at ϩ60 mV (pipette potential) except when gathering data for I-V plots to determine single-channel conductance.…”
Section: Methodsmentioning
confidence: 99%